Dr Haiquan Chen: clinical significance of RET fusion gene for patients with NSCLC - Feng, Zhihua (Translational Lung Cancer Research; Vol 2, No 1 (February 14, 2013): Translational Lung Cancer Research, 2013)
Recent researches found RET fusion gene, exists in part of the NSCLC subgroup. Due to limited knowledge in this kind of oncology, a study aiming to determine the clinicopathologic characteristics of the RET fusion gene in NSCLC patient was carried out by experts such as Dr Rui Wang and Dr Haiquan Chen from Fudan University Cancer Center in Shanghai. The study was published in Journal of Clinical Oncology (Nov. 13, 2012).